2018
DOI: 10.3389/fnhum.2018.00083
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Blood Pressure With Spinal Cord Epidural Stimulation After Severe Spinal Cord Injury

Abstract: Chronic low blood pressure and orthostatic hypotension remain challenging clinical issues after severe spinal cord injury (SCI), affecting health, rehabilitation, and quality of life. We previously reported that targeted lumbosacral spinal cord epidural stimulation (scES) could promote stand and step functions and restore voluntary movement in patients with chronic motor complete SCI. This study addresses the effects of targeted scES for cardiovascular function (CV-scES) in individuals with severe SCI who suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 37 publications
3
90
1
2
Order By: Relevance
“…[126][127][128][129][130][131][132] During the course of some of these initial studies to restore stepping and standing using lumbosacral scES in motor complete humans, investigators discovered that individuals with cardiovascular dysfunction showed increases in SBP with stimulation. [133][134][135] This response also allowed upright standing by ameliorating orthostatic hypotension. Further study identified specific cardiovascular-targeted scES configurations (CV-scES, L1-S4/5 spinal cord) that did not elicit motor activity and maintained SBP within a normal range during orthostatic stress.…”
Section: Epidural Stimulationmentioning
confidence: 98%
See 1 more Smart Citation
“…[126][127][128][129][130][131][132] During the course of some of these initial studies to restore stepping and standing using lumbosacral scES in motor complete humans, investigators discovered that individuals with cardiovascular dysfunction showed increases in SBP with stimulation. [133][134][135] This response also allowed upright standing by ameliorating orthostatic hypotension. Further study identified specific cardiovascular-targeted scES configurations (CV-scES, L1-S4/5 spinal cord) that did not elicit motor activity and maintained SBP within a normal range during orthostatic stress.…”
Section: Epidural Stimulationmentioning
confidence: 98%
“…Further study identified specific cardiovascular-targeted scES configurations (CV-scES, L1-S4/5 spinal cord) that did not elicit motor activity and maintained SBP within a normal range during orthostatic stress. 135 Importantly, orthostatic blood pressure was maintained after eighty sessions of CV-scES in four participants, even with the stimulator turned off ( ►Fig. 2).…”
Section: Epidural Stimulationmentioning
confidence: 99%
“…Orthostatic hypotension is a common problem in individuals with a SCI . EES directed at improving cardiovascular function in individuals with SCI demonstrated elevation and maintenance of mean arterial pressures to normative ranges across sessions and subjects . In addition, the use of EES with rehabilitation showed improvements in body composition such as lean body mass with decreases in percentage of body fat, particularly android body fat, and android/gynoid ratios when compared to baseline values .…”
Section: Alternative Approaches and Strategiesmentioning
confidence: 98%
“…Implanted electrodes for electrical stimulation with intensive neurorehabilitation could partially restored standing and walking abilities in patients with complete chronic SCI [42,43]. In such cases, improved reflexive voiding efficiency [44], enhanced cardiovascular fitness and body composition [45], better neurological recovery [46] that supported the activities of daily living [47], and reduced that elevated blood pressures to normal ranges from a chronic hypotensive state [48] were observed.…”
Section: Neurostimulation/neuromodulation and The Brain-computer Intementioning
confidence: 99%